1977
DOI: 10.1084/jem.146.2.368
|View full text |Cite
|
Sign up to set email alerts
|

A suppressor T cell in the human mixed lymphocyte reaction.

Abstract: Lymphocytes from an HLA-B7 DW2 homozygous multiparous woman, J.H., failed to respond in the mixed lymphocyte reaction to lymphocytes from her DW1 homozygous husband, W.H., and certain other homozygous typing cells. J.H. lymphocytes could suppress the response of HLA matched responders to W.H. This effect was shown to be radiosensitive and due to a T cell. The suppressor cell showed antigen specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…Although the suppressive activity detected in these experiments appears to be nongenetically restricted in most cases, the simultaneous presence of an additional, undetected, genetically restricted suppressor is not eliminated. A genetically restricted suppressor cell (31) (23), but the stimulator capacity of group III patients' cells also appeared to depend on the mitomycin C sensitivity of the suppressor cell activity in the population. The suppressor cell activity of group III patient cells appears to be mitomycin sensitive during the 4-to 6-d period and resistant at later periods.…”
Section: Resultsmentioning
confidence: 94%
“…Although the suppressive activity detected in these experiments appears to be nongenetically restricted in most cases, the simultaneous presence of an additional, undetected, genetically restricted suppressor is not eliminated. A genetically restricted suppressor cell (31) (23), but the stimulator capacity of group III patients' cells also appeared to depend on the mitomycin C sensitivity of the suppressor cell activity in the population. The suppressor cell activity of group III patient cells appears to be mitomycin sensitive during the 4-to 6-d period and resistant at later periods.…”
Section: Resultsmentioning
confidence: 94%
“…Several recent studies have suggested that suppressor cell activity may be involved in pregnancy-associated decreased immune responses (9,(20)(21)(22). For example, Clark and MacDermott (20) have presented evidence for the presence of a suppressor cell(s) for paternal antigens in the mixed lymphocyte cultures of the cells from the draining lymph nodes of the uterus, although the type of the suppressor cell(s) was not defined in this study.…”
Section: Discussionmentioning
confidence: 66%
“…Adoptive transfer of spleen cells from multiparous mice to virgin recipients has also been reported to induce tolerance to the H-Y antigen in male skin graft and this appears to be mediated by suppressor T cells (21). Similar suppressor T cells have also been reported in humans (22). In addition, it has been shown by Hamilton and Hellstr/Sm (9) that the mixtures of lymphocytes from pregnant and virgin mice are less reactive to alloantigen stimulation than the individual cell population alone, suggesting the presence of nonspecific suppressor cells in pregnant mice.…”
Section: Discussionmentioning
confidence: 71%
“…This may indicate a disturbance in at least a fraction of the T-cells, e.g. either a deficit of allogeneic-reacting T-lymphocytes or an increased amount of suppressor T-cells (MCMICHAEL & SASAZUKI 1977).…”
Section: Discussionmentioning
confidence: 99%